Development of a Self-Efficacy Scale for Vocational School - I Kadek Febry Saputra; Ni Ketut Suarni; Nyoman Dantes Dantes (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This study aims to develop a self-efficacy scale instrument for Vocational High School students as well as to determine the validity of the instrument points and the instrument reliability of the experts and practitioners. The type of research used is research and development (R&D), the research model used is Four-D (4D). The 4D model consists of four stages of research namely define, design, develop, and disseminate. Analysis of the data used is to test the validity of manual book product content with the Lawshe CVR and CVI formulas. Tests carried out by 5 experts or experts who are competent in the field of Counseling and Psychological Guidance. The results of the research based on content validity analysis are the per-item CVR values obtained between +1 to 0 (CVR> 0). Furthermore, the results of the Lawshe CVI analysis obtained a score of 0.96 greater than 0 (0.96> 0). Based on the analysis of these data means the value of the validity of the instrument content is high and for the reliability results obtained at 0.78> 0.60 thus all items of the questionnaire are declared reliable